YOUNG, ARMED REBELS. A LOOK AT THE IDENTITY AND MEMORY OF YOUNG REBELS DURING THE TRANSITION - Rosas Aravena, Pedro (Revista de Historia Social y de las Mentalidades, 2011)
The affirmation of the Italian historian Alessandro Portelli, is situated with full “epistemological right” in one of the two most powerful historiographical tides of the 19th and 20th centuries. the first of these high tides would reach the German historiographical shores in the second half of the 19th century with the figure of Leopold Von Ranke and historical positivism; characterized by the patient and neat harvest of apparently unpolluted and "objective" facts produced by the enlightened and armed dominant elites; illuminated and possessed of god and blood.